Measures related to operator ideals and Sparr's interpolation methods (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2008)
We establish an estimate for the outer measure $γ_I(T)$ and the inner measure $β_I(T)$ of an operator $T$ acting between some intermediate spaces constructed for $n$-tuples of Banach spaces. We also show that many operator ideals have the strong interpolation property for Sparr's interpolation methods.